Hubungan antara Smoker Identity dan Entitativity Group pada Emerging Adulthood di Kota Bandung - Refina Salma Michelia; Stephani Raihana Hamdan (Bandung Conference Series: Psychology Science, 2023)
Abstract. Smoker identity is the extent to which an individual can identify himself as a smoker and live the smoking behavior. Smoking behavior is a behavior that is contrary to the views of society and often gets a negative view. To protect the identity of smokers, smokers tend to seek refuge within a group. To form a group that can support each other, it takes an entitytivity group that can be formed by 3 aspects, namely similarity, proximity and common fate. The purpose of this study was to obtain empirical data regarding the relationship between smoker identity and group entitativity in emerging adulthood in Bandung. Data was collected using measuring instruments, namely the smoker identity scale (SIS) and the entitativity group. The method used in this research is correlational. The research subjects are active smokers aged 18-25 years (emerging adulthood) in the city of Bandung, totaling 300 people. Based on the results of data processing, it was found that there was a low positive relationship between smoker identity and entitativity group (0.231). That is, the weaker the smoker identity you have, the lower the entity group you have. Abstrak. Smoker identity merupakan sejauh mana individu dapat mengidentifikasi dirinya sebagai perokok dan menghayati perilaku merokok tersebut. Perilaku merokok merupakan perilaku yang bertentangan dengan pandangan masyarakat dan seringkali mendapat pandangan negatif. Untuk melindungi identitas perokoknya, para perokok cenderung mencari perlindungan di dalam suatu kelompok. Untuk membentuk suatu kelompok yang dapat saling mendukung dibutuhkan entitativity group yang dapat dibentuk oleh 3 aspek yaitu similarity, proximity dan common fate. Tujuan dari penelitian ini adalah memperoleh data empiris mengenai hubungan antara smoker identity dan entitativity group pada emerging adulthood di Kota Bandung. Pengumpulan data dilakukan dengan menggunakan alat ukur yaitu smoker identity scale (SIS) dan entitativity group. Metode yang digunakan pada penelitian ini adalah korelasional. Subjek penelitiannya adalah perokok aktif berusia 18-25 tahun (emerging adulthood) di Kota Bandung yang berjumlah 300 orang. Berdasarkan hasil pengolahan data, didapati hasil hubungan positif yang rendah antara smoker identity dan entitativity group (0,231). Artinya, semakin lemah smoker identity yang dimiliki maka semakin rendah entitativity group yang dimiliki.